Standardized evaluation methodology and reference database for evaluating IVUS image segmentation - Balocco, Simone; Gatta, Carlo; Ciompi, Francesco; Wahle, Andreas; Radeva, Petia; Carlier, Stephane; Unal, Gozde; Sanidas, Elias; Mauri, Josepa; Carillo, Xavier; Kovarnik, Tomas; Wang, Ching-Wei; et al. (Computerized medical imaging and graphics, 2014)
This paper describes an evaluation framework that allows a standardized and quantitative comparison of IVUS lumen and media segmentation algorithms. This framework has been introduced at the MICCAI 2011 Computing and Visualization for (Intra)Vascular Imaging (CVII) workshop, comparing the results of eight teams that participated. We describe the available data-base comprising of multi-center, multi-vendor and multi-frequency IVUS datasets, their acquisition, the creation of the reference standard and the evaluation measures. The approaches address segmentation of the lumen, the media, or both borders; semi- or fully-automatic operation; and 2-D vs. 3-D methodology. Three performance measures for quantitative analysis have been proposed. The results of the evaluation indicate that segmentation of the vessel lumen and media is possible with an accuracy that is comparable to manual annotation when semi-automatic methods are used, as well as encouraging results can be obtained also in case of fully-automatic segmentation. The analysis performed in this paper also highlights the challenges in IVUS segmentation that remains to be solved.
Keywords: Coronary Artery Disease; Image Interpretation, Computer-Assisted; Databases, Factual; Internationality; Ultrasonography, Interventional; databáze faktografické; internacionalita; Practice Guidelines as Topic; referenční hodnoty; reprodukovatelnost výsledků; IVUS (intravascular ultrasound); nemoci koronárních tepen; intervenční ultrasonografie; Reproducibility of Results; Image segmentation; Reference Values; lidé; Humans; Evaluation framework; Sensitivity and Specificity; senzitivita a specificita; Algorithm comparison; interpretace obrazu počítačem; směrnice pro lékařskou praxi jako téma